Polycystic ovary syndrome with hyperandrogenism as a risk factor for non‐obese non‐alcoholic fatty liver disease - Kim, J. J.; Kim, D.; Yim, J. Y.; Kang, J. H.; Han, K. H.; Kim, S. M.; Hwang, K. R.; Ku, S. Y.; Suh, C. S.; Kim, S. H.; Choi, Y. M. (Alimentary pharmacology & therapeutics, 2017)
Summary Background Non‐alcoholic fatty liver disease (NAFLD) is known to be associated with polycystic ovary syndrome (PCOS). However, most studies investigated the prevalence of NAFLD in obese PCOS patients. Aim To compare the prevalence of non‐obese NAFLD in women with or without PCOS, and to assess an independent association between PCOS and NAFLD in a non‐obese Asian cohort. Methods This was a case–control study using a prospective PCOS cohort. After subjects with other potential causes of chronic liver disease were excluded, 275 non‐obese women with PCOS and 892 non‐obese controls were enrolled. NAFLD was determined by hepatic ultrasonography. Main outcomes were the prevalence of NAFLD on hepatic ultrasonography between non‐obese women with or without PCOS, and an independent association between non‐obese NAFLD and PCOS. Results Non‐obese women with PCOS had a significantly higher prevalence of NAFLD than those without PCOS (5.5% vs. 2.8%, P = 0.027). PCOS was associated with non‐obese NAFLD (odds ratio: 2.62, 95% confidence intervals: 1.25–5.48) after adjustment for age and body mass index (BMI). In women with PCOS, the level of androgenicity represented by free testosterone or free androgen index was associated with NAFLD after adjustment for age, BMI, lipid profile, insulin resistance or glycaemic status. Conclusions Non‐obese NAFLD is more prevalent in women with polycystic ovary syndrome than in those without. In non‐obese patients with polycystic ovary syndrome, hyperandrogenemia may be an independent risk factor for non‐obese NAFLD. Linked ContentThis article is linked to Q. Pang et al and L. Zhou and H. Jin paper. To view this article visit https://doi.org/10.1111/apt.14159.